Analysis of Whistler‐Mode and Z‐Mode Emission in the Juno Primary Mission. Issue 11 (19th November 2021) - Menietti, J. D.; Averkamp, T. F.; Kurth, W. S.; Imai, M.; Faden, J. B.; Hospodarsky, G. B.; Santolik, O.; Clark, G.; Allegrini, F.; Elliott, S. S.; Sulaiman, A. H.; Bolton, S. J.
Abstract: At the end of the Juno primary mission, we report observations of whistler mode chorus and Z‐mode emission. The Juno orbits are evolving and much better coverage of the whistler mode chorus source region has resulted since the earlier surveys. Bursty chorus emission extending to ∼30° latitude and to frequencies less than the lower hybrid frequency near the source region imply high electron energies (>100 keV). Average chorus intensity levels peak at ∼10 −3  nT 2 near M‐shell of 8–9 and magnetic latitude of ∼5°. Z‐mode emission is identified at higher latitudes generally near and inward of the Io torus with intensity levels as much as two orders of magnitude higher than Z‐mode emissions observed at Saturn. Inferred source regions for the Z‐mode are consistent with the inner edge of the Io torus and with auroral field lines that may also support Jovian kilometric and decametric emission. Parametric fitting functions are evaluated for both whistler mode chorus and Z‐mode, describing wave intensity as a function of frequency, magnetic latitude, and M‐shell. Both whistler mode and Z‐mode waves may have significant impact on electron scattering and acceleration at Jupiter as recent models indicate. Key Points: Jovian whistler‐mode chorus and Z‐mode intensity distributions are surveyed and analyzed at the end of the Juno primary mission Bursty low frequency whistler mode emission implies electrons energies exceeding 100 keV Jovian whistler mode chorus and Z‐mode intensity are parametrically fit to frequency, M‐shell, and mag‐latitude